Dementia risk by combinations of metabolic diseases and body mass index: Japan Gerontological Evaluation Study Cohort Study. Issue 1 (2nd July 2019) - Yokomichi, Hiroshi; Kondo, Katsunori; Nagamine, Yuiko; Yamagata, Zentaro; Kondo, Naoki
Abstract: Aims/Introduction: To compare the dementia risk associated with pre‐existing diabetes, hypertension, dyslipidemia, obesity (body mass index [BMI] ≥25 kg/m 2 ) and underweight (BMI <18.5 kg/m 2 ) among older adults. We also explored the dementia risk associated with combinations of metabolic diseases and BMI. Materials and Methods: We used data from the Japan Gerontological Evaluation Study. Participants completed a health checkup in 2010 and were followed for 5.8 years on average. Dementia was measured by municipal long‐term care insurance registration. Diabetes, hypertension, dyslipidemia, obesity and underweight were diagnosed by medication use or health examination results. We calculated the incidence of dementia and adjusted hazard ratios (HRs). Results: Among 3, 696 participating older adults, 338 developed dementia. Adjusted HRs (95% confidence intervals) in men and women (reference: those without corresponding disease of normal weight) were as follows: 2.22 (1.26–3.90) and 2.00 (1.07–3.74) for diabetes; 0.56 (0.29–1.10) and 1.05 (0.64–1.71) for hypertension; 1.30 (0.87–1.94) and 0.73 (0.49–1.08) for dyslipidemia; 0.73 (0.42–1.28) and 0.82 (0.49–1.37) for BMI of 25–29.9 kg/m 2 ; and 1.04 (0.51–2.10) and 1.72 (1.05–2.81) for underweight. Dementia risk was significantly higher in underweight men with dyslipidemia (HR 4.15, 95% CI 1.79–9.63) compared with normal‐weight men without dyslipidemia, and in underweight women with hypertension (HR 3.79, 1.55–9.28) compared with normal‐weight women without hypertension. Dementia incidence was highest among underweight older adults with hypertension followed by dyslipidemia. Conclusions: Among Japanese older adults, underweight and prevalent diabetes are risk factors for developing dementia. Lower BMI is also associated with a higher incidence of dementia. Abstract : The Japan Gerontological Evaluation Study, a cohort study, compared the risks of dementia among varied profiles of metabolic disease and body mass index in Japanese older adults. Underweight and prevalent diabetes were risk factors for developing dementia. Lower body mass index was associated with higher dementia incidence.